The Politics of Women’s Rights in Iran - Abbas Barzegar (International Institute of Islamic Thought, 2010)
Firmly situated in the field of legal anthropology, Arzoo Osanloo’s The Politics of Women’s Rights in Iran is an ethnographic treatment of women’s rights discourse in contemporary Iran. It is concerned with unraveling the assumed paradoxes involved in administering a republican theocracy that attempts to incorporate both divinely inspired legal injunctions and representative forms of governance. Whereas many conversations concerning human rights and Islam are drowned in contention, normativity, and exegetical speculation, Osanloo’s contribution steadily manages to remain above the fray. This is done by placing the discourse of women’s rights within the cultural context of globalization and post-colonialism and yet still identifying its local, embodied practice within the shifting political dynamics of post-revolutionary Iran. To this end, through exploring the lives of upper-middle class women in Tehran and their encounters with the emerging Islamo-republican state, the author explores the “conditions [that] have allowed for the discussion of rights to materialize in a language that was unacceptable just after the revolution…” (p. 7), while paying close attention to the ways in which contemporary Iran represents a vernacular modernity expressed through “a hybrid discourse that locates a distinctive form of modernity at the juncture of Islamic revivalism and Western political and legal institutions” (p. 8). Her theoretical and methodological approach, which incorporates elements of post-colonialism and post-modernism, is presented in a short introudction. Guiding concepts such as “rights as discursive practice,” “dialogical sites,” and “subjectivization” thus readily inform her mobilization and treatment of the data. Thankfully, her concern for methodological precision does not obscure or consume the narrative form through which she puts forth her thesis in the remainder of the text ...